2018
DOI: 10.1242/jeb.174540
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to DNA damage and enhanced DNA repair capacity in the hypoxia-tolerant blind mole rat, Spalax

Abstract: Blind mole rats of the genus are the only mammalian species to date for which spontaneous cancer has never been reported and resistance to carcinogen-induced cancers has been demonstrated. However, the underlying mechanisms are still poorly understood. The fact that spp. are also hypoxia-tolerant and long-lived species implies the presence of molecular adaptations to prevent genomic instability, which underlies both cancer and aging. We previously demonstrated the upregulation of transcripts related to DNA rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 49 publications
(54 reference statements)
2
26
0
Order By: Relevance
“…Persistent DNA damage is required to induce an inflammatory response and SASP in senescent cells (Rodier et al, ; Wang et al, ). Spalax fibroblasts demonstrated resistance to acute DNA damage and high DNA repair capability (Domankevich et al, ); therefore, we investigated the level of DDR in Spalax fibroblasts undergoing replicative and premature senescence. Since phosphorylated H2AX histone (γH2AX) is a reliable indicator of DNA double‐strand breaks (DSBs) (Sharma, Singh, & Almasan, ), we used γH2AX foci quantification in our experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Persistent DNA damage is required to induce an inflammatory response and SASP in senescent cells (Rodier et al, ; Wang et al, ). Spalax fibroblasts demonstrated resistance to acute DNA damage and high DNA repair capability (Domankevich et al, ); therefore, we investigated the level of DDR in Spalax fibroblasts undergoing replicative and premature senescence. Since phosphorylated H2AX histone (γH2AX) is a reliable indicator of DNA double‐strand breaks (DSBs) (Sharma, Singh, & Almasan, ), we used γH2AX foci quantification in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Spalax fibroblasts, similarly to human and mouse cells, stopped dividing and underwent irreversible proliferative arrest; moreover, they showed a positive SA‐β‐Gal staining and increased gene expression of p21, p16, and p53, the important markers of senescence. Recently, we demonstrated that Spalax skin fibroblasts in culture resist several types of genotoxic insult (H 2 O 2 , UV‐C radiation, etoposide in high doses) and exhibit an enhanced DNA repair capacity compared with Rattus fibroblasts, evaluated by γH2AX immunofluorescence, comet assay and host cell reactivation assay (Domankevich et al, ). In addition, our previous studies demonstrated significant enrichment of DNA replication and Fanconi anemia pathways in Spalax brain, muscle, and liver transcriptomes (Altwasser et al, ; Malik et al, ; Schmidt et al, ), that contribute to DNA stability during replicative and genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be exacerbated in certain caves (e.g., Cueva Chica and El Pachó n) that serve as roosting sites for large numbers of bats that bring organic materials (guano and dead bodies) into the water on a daily basis [25,70]. Interestingly, an enhancement of DNA repair capacity has also been identified in the blind mole rat, Spalax carmeli, linked with its hypoxia tolerance [26]. An additional feature of certain cave systems that might cause elevated DNA damage is the natural radioactive gas, radon 222 Rn, which is released from certain rocks and concentrated in caves [71].…”
Section: Evolution Of Dna Repair Systems In Extreme Aphotic Environmentsmentioning
confidence: 99%
“…Cave-dwelling organisms share a set of striking phenotypes-so-called ''troglomorphisms,'' including notably complete loss of the eyes and body pigmentation. In certain cases, alterations in DNA repair function have also been reported [25][26][27]. For example, enhanced DNA repair has been encountered in blind cave forms of Astyanax mexicanus [25].…”
Section: Introductionmentioning
confidence: 99%